2016
DOI: 10.5194/acp-16-597-2016
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter in the tropical environment: monsoonal effects, source apportionment, and health risk assessment

Abstract: The health implications of PM 2.5 in the tropical region of Southeast Asia (SEA) are significant as PM 2.5 can pose serious health concerns. PM 2.5 concentration and sources here are strongly influenced by changes in the monsoon regime from the south-west quadrant to the north-east quadrant in the region. In this work, PM 2.5 samples were collected at a semi-urban area using a high-volume air sampler at different seasons on 24 h basis. Analysis of trace elements and water-soluble ions was performed using induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 116 publications
7
100
2
Order By: Relevance
“…For the carcinogenic risks, industrial coal combustion was found to be the largest contributor, followed by biomass burning sources. Similar findings were reported by Khan et al (2016) in the tropical environment in Malaysia. Secondary inorganic aerosols contributed approximately 25 % of the PM 2.5 mass, but they posed little carcinogenic risk.…”
Section: Health Risk Assessment Of Resolved Pm Sourcessupporting
confidence: 79%
See 1 more Smart Citation
“…For the carcinogenic risks, industrial coal combustion was found to be the largest contributor, followed by biomass burning sources. Similar findings were reported by Khan et al (2016) in the tropical environment in Malaysia. Secondary inorganic aerosols contributed approximately 25 % of the PM 2.5 mass, but they posed little carcinogenic risk.…”
Section: Health Risk Assessment Of Resolved Pm Sourcessupporting
confidence: 79%
“…Moreover, airborne particles and associated trace elements originate from various emission sources, such as motor vehicles, metallurgical industry, coal burning and soil dust, and could be emitted in a broad size range. Studies suggest that some particle sources are more harmful than others and recommend that controlling some of the specific sources of PM could be a more effective way for protecting public health (Bell et al, 2014;Khan et al, 2016). Airborne particle health risk assessment is increasingly dependent on the source apportionment of PM using chemical component data.…”
Section: Introductionmentioning
confidence: 99%
“…For the carcinogenic risks, industrial coal 5 combustion was found the largest contributor, followed by biomass burning source. Similar findings were reported by Khan et al (2016) in the a tropical environment in Malaysia. Secondary inorganic aerosols contributed approximately 25% of the PM 2.5 mass, but they posed little carcinogenic risk.…”
Section: Health Risk Assessment Of Resolved Pm Sourcessupporting
confidence: 79%
“…protecting public health (Bell et al, 2014;Khan et al, 2016). Airborne particle health risk assessment is increasingly depended on the source apportionment of PM using chemical component data.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed high As, Pb, and Zn concentrations in most Southeast Asia. The sources of As, Pb, and Zn may originate from coal-fired power, lead related industries and vehicle (Santoso et al, 2011;Wimolwattanapun et al, 2011;Khan et al, 2016).…”
Section: Backward Trajectory Analysismentioning
confidence: 99%